2018
DOI: 10.1038/s41598-018-34470-z
|View full text |Cite
|
Sign up to set email alerts
|

The adaptive value of camouflage and colour change in a polymorphic prawn

Abstract: Camouflage has been a textbook example of natural selection and adaptation since the time of the earliest evolutionists. However, aside from correlational evidence and studies using artificial dummy prey, experiments directly showing that better camouflaged prey to predator vision are at reduced risk of attack are lacking. Here, we show that the level of camouflage achieved through colour adjustments towards the appearance of seaweed habitats is adaptive in reducing predation pressure in the prawn Hippolyte ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 75 publications
2
29
0
Order By: Relevance
“…food and shelter 43 ). This would allow the exploitation of a wider range of resources within structurally complex habitats, potentially reducing intra-specific competition 60 and predation risk 61 . Concurrently, behavioural preferences facilitate camouflage over time-scales when colour change is too slow.…”
Section: Discussionmentioning
confidence: 99%
“…food and shelter 43 ). This would allow the exploitation of a wider range of resources within structurally complex habitats, potentially reducing intra-specific competition 60 and predation risk 61 . Concurrently, behavioural preferences facilitate camouflage over time-scales when colour change is too slow.…”
Section: Discussionmentioning
confidence: 99%
“…Greater background matching could also occur if individuals are exposed to different substrates as soon as they settle from the plankton, when, in accordance with their life history, there would be the greatest need for habitat matching. The gradual changes in response to the background observed here (Fig 2C,D) may correspond to improvements in camouflage (Fig 3) and, potentially, survival (17,18), but because colour change in European lobster is relatively slow (Figs 2 and 3), any benefit would require pre-conditioning individuals for the habitat they are released into. Post-release survival will also depend on the habitat and predators present at the release site.…”
Section: Discussionmentioning
confidence: 81%
“…It is likely that many juvenile crustaceans are phenotypically plastic with the ability to match the environment in which they settle (15,16). Such plasticity in background matching should confer a substantial survival advantage (17,18), and is likely to be particularly important for species and life stages that otherwise have limited anti-predator defences. The benefits of understanding camouflage and how it works have long been realised in applied areas such as the military and art and design (19,20), and colour change applications are growing in other fields, such as biomimicry (21) and animal welfare (22).…”
Section: Introductionmentioning
confidence: 99%
“…In nature, animal camouflage with genetically determined coloration may be more widespread than the camouflage determined by morphological or physiological colour changeability, which is observed in cuttlefish, cephalopods and crabs [71]. However, most studies of animal camouflage showing fine-tuning to local backgrounds have dealt with species exhibiting colour changeability [12,14]; the exceptions are studies of melanin-pigmented fur or skin among vertebrates [21,72]. Thus, our study is one of few that have demonstrated finely tuned background-matching camouflage in detail in a species with genetically determined coloration.…”
Section: Discussion (A) Fine-tuning Of Body Colour To Local Backgrounmentioning
confidence: 99%
“…Recent advances in optical analysis techniques and knowledge of colour perception have allowed modelling of predator vision and consideration of how coloration might be perceived by natural predators [12,16]. Some studies have used vision models to test concealment [17][18][19][20][21]; however, tests for optimal camouflage using actual predators remain rare [13,14]. Therefore, the evolutionary fine-tuning of cryptic coloration to match local backgrounds has not yet been fully demonstrated, although it is a fundamental prediction of anti-predator adaptations.…”
Section: Introductionmentioning
confidence: 99%